AESTHETICS, CREATIVITY, AND MYSTICISM: AN INVESTIGATION OF THREE MODES OF CONSCIOUSNESS. - Frishkopf, Michael (Zygon: Journal of Religion & Science, 2019)
This essay explores the universal nature of aesthetic, creative, and mystical experience, tracing some essential interrelations among the three. Enlarging upon the work of anthropologist Jacques Maquet, I speculate that "sensory fixedness" is both necessary and sufficient to achieve aesthetic experience, and that the unification of mind engendered by sensory fixedness is the essential source of aesthetic power. Therefore, the role of the aesthetic object (construed broadly) is either as an arbitrary sensory focusing mechanism, or as the physical embodiment of a gestalt facilitating fixedness; the first category is merely attractive, while the second contains all that is truly great in art (visual and auditory). I suggest further that as both creative inspiration and mystical experience result from fixedness, both are related to aesthetic experience. However, while aesthetic experience is rooted in sensation, mystical and creative experience, though often prepared by sensory fixedness, may transcend the sensory domain altogether toward more abstract forms of mental fixedness.